Pengaruh Kecerdasan Emosional Terhadap Hasil Belajar Matematika Siswa Sekolah Dasar - Yakin Akbar Asikin; Istiqamah Istiqamah; Ayumi Abbas (Universitas Muhammadiyah Ponorogo, 2022)
This study aims to determine the effect of emotional intelligence on the mathematics learning outcomes of fourth-grade students of SD Inpres Kalabahi Tengah VI. This study uses ex-post-facto quantitative research, with the independent variable being emotional intelligence and the dependent variable being learning outcomes. The population and samples used were all fourth-grade students of SD Inpres Kalabahi Tengah VI, Alor, East Nusa Tenggara with a total of 20 students. The instrument used in this research is the emotional intelligence scale and documents, while the data analysis technique uses descriptive and inferential statistical analysis with simple regression analysis. The results of this study found that (a) the results of the descriptive analysis resulted in the finding that the emotional intelligence of the fourth-grade students of SD Inpres Kalabahi Tengah VI was in the moderate category with a percentage of 90%, while the mathematics learning outcomes of the fourth graders of SD Inpres Kalabahi Tengah VI were in the category medium with a percentage of 100%; (b) the results of the inferential analysis found that the regression equation obtained Y= 81.693 + 0.027X; (c) significant test results obtained a significant value of 0.738 where a significant value 0.05 (0.738 0.05), thus accepted; (d) the conclusion of this study shows that there is no influence of emotional intelligence on mathematics learning outcomes for fourth-grade students at SD Inpres Kalabahi Tengah VI, Alor, East Nusa Tenggara.